Association of dietary and circulating antioxidant vitamins with metabolic syndrome: an observational and Mendelian randomization study - Sun, Qian; Fan, Zhixing; Yao, Fangfang; Zhao, Xiaojing; Jiang, Min; Yang, Mudan; Mao, Menglu; Yang, Chaojun (Frontiers in Endocrinology, 2024)
The objective of this study was to investigate the associations between of dietary orand circulating serum antioxidant vitamins andwith metabolic syndrome (MetS), and to assess causality using Mendelian randomization (MR).Methods: This study included 10,308 participants from the National Health and Nutrition Examination Survey. The associations of vitamins A, C, E and carotenoids with MetS were assessed using multivariable weighted logistic regression analysis.Subsequently, the MR approach was employed to test the causal associations, with inverse variance weighted (IVW) serving as the primary analysis.Results: Observationally, dietary vitamin A (OR=0.852, 95%CI: 0.727-0.999), C (OR=0.802, 95%CI: 0.675-0.952), carotene (OR=0.832, 95%CI: 0.706-0.982), and βcarotene (OR=0.838, 95%CI: 0.706-0.995) in quartile 4 had lower incidents of MetS, when compared to quartile 1. Circulating Serum vitamin C and carotene were also present inversely associated with MetS, while the vitamin A and E both increased this risk. IVW-MR confirmed the associations of dietary vitamin A (OR=0.920, 95%CI: 0.861-0.984), vitamin C (OR=0.905, 95%CI: 0.836-0.979) and carotene (OR=0.918, 95%CI: 0.865-0.974) with MetS. However, there was only circulating β-carotene (OR=0.909, 95%CI: 0.857-0.965) was found to be causally associated with MetS.Observational and MR studies have shown that adequate dietary intake of vitamin A, C and carotenoids may help to reduce the risk of MetS.